If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 4 = -2y + -8 Reorder the terms: 4 + 4y = -2y + -8 Reorder the terms: 4 + 4y = -8 + -2y Solving 4 + 4y = -8 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. 4 + 4y + 2y = -8 + -2y + 2y Combine like terms: 4y + 2y = 6y 4 + 6y = -8 + -2y + 2y Combine like terms: -2y + 2y = 0 4 + 6y = -8 + 0 4 + 6y = -8 Add '-4' to each side of the equation. 4 + -4 + 6y = -8 + -4 Combine like terms: 4 + -4 = 0 0 + 6y = -8 + -4 6y = -8 + -4 Combine like terms: -8 + -4 = -12 6y = -12 Divide each side by '6'. y = -2 Simplifying y = -2
| 0.19y+0.05(y+2000)=1540 | | 63d+63n=5.05 | | -21-x-2x=30 | | 9.12/x=0.2 | | 63(n+d)=5.05 | | 8t+1/9=t+9/18+t-7/18 | | 3xy+2x+3x= | | -(x+4)-2x+3=-16 | | 2x+3x+400=1050 | | 4b+3=2b | | 49x^4+112x^2+64=0 | | M+t=r | | 25(x+39)=b | | 3.5(3x-8)=x | | -(3-15y)=12 | | -(6x-3)=-9 | | 3-6x=2+6x | | 1/3(12x-36)+4=x+25 | | 5k-3/2=4 | | 2b+5=b+13 | | xy-4x=12 | | 6y-9(5y-8)= | | -3x-8+2x=8 | | 4.6+10m=8.81 | | 3(2x-2)+5=6(x+1) | | -9(v+2)+4v+7=8v+8 | | 76x-9=4x | | -3x+9x-41=97 | | 5x-2=1+3x | | X+21=3X-1 | | 22+6z+95=b | | 2(2x+3x)-10=30 |